2001
DOI: 10.1097/00041327-200106000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disorders: A Risk Factor for Pseudotumor Cerebri?

Abstract: Sleep-related breathing problems were common in our patients with idiopathic intracranial hypertension. Obesity was common in these patients and may be playing a causative role in sleep apnea and idiopathic intracranial hypertension. It is suggested that idiopathic intracranial hypertension patients who have symptoms of sleep disturbance should be further evaluated for the presence of sleep-related breathing problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 22 publications
1
43
0
Order By: Relevance
“…Wang et al [13] compared the clinical features of 25 patients with IIHWOP with those exhibiting chronic daily headache (CDH) but with normal CSF pressure, and no difference in headache profile was found. Besides clinical presentation, IIH and CM also share some relevant risk factors such as S24 Neurol Sci (2015) 36 (Suppl 1):S23-S28 female gender, obesity and sleep disturbances [44][45][46] and both show a higher prevalence of allodynic symptoms [47][48][49][50]. Topiramate, a drug with documented efficacy in CM [51,52] that shares with acetazolamide the inhibition of carbonic anhydrase isoenzyme [53], has been found as effective as acetazolamide in IIH treatment [54], suggesting that the topiramate efficacy in CM could be mediated, at least partially, by an acetazolamide-like CSF pressure lowering effect.…”
Section: Idiopathic Intracranial Hypertensionmentioning
confidence: 99%
“…Wang et al [13] compared the clinical features of 25 patients with IIHWOP with those exhibiting chronic daily headache (CDH) but with normal CSF pressure, and no difference in headache profile was found. Besides clinical presentation, IIH and CM also share some relevant risk factors such as S24 Neurol Sci (2015) 36 (Suppl 1):S23-S28 female gender, obesity and sleep disturbances [44][45][46] and both show a higher prevalence of allodynic symptoms [47][48][49][50]. Topiramate, a drug with documented efficacy in CM [51,52] that shares with acetazolamide the inhibition of carbonic anhydrase isoenzyme [53], has been found as effective as acetazolamide in IIH treatment [54], suggesting that the topiramate efficacy in CM could be mediated, at least partially, by an acetazolamide-like CSF pressure lowering effect.…”
Section: Idiopathic Intracranial Hypertensionmentioning
confidence: 99%
“…In children with CND submitted to ABI without associated UR issues, the relatively low pressure normally exerted by the CSF on the dural sutures, coupled with the particular vascularity of the dura allow for robust wound healing, and leading to a successful closure with no CSF collection in the vast majority of cases, even with standard surgical techniques. Conversely, children with significant UR issues and OSA often with secondary intracranial hypertension (SIH) (12)(13)(14)(15)(16), must be considered at higher risk for a CSF leak postoperatively. Indeed, this particular cohort of children need an individualized assessment of their respiratory problems with emphasis on identifying significant comorbidities responsible for idiopathic intracranial hypertension (IIH) or secondary intracranial hypertension (SIH) before the decision for ABI is confirmed.…”
Section: Resultsmentioning
confidence: 99%
“…[94] Cerebral venous thrombosis has been found in 11.4% of patients who were presumed to have IIH. [95] IIH has been associated with many etiologies such as exposition to a number of drugs (vitamin A, growth hormone, steroids, minocycline and tetracycline, sulphasalazine, etc…), [96][97][98][99][100][101][102] Behçet's Disease, [103] arteriovenous malformations, [104] sleep disturbances including obstructive sleep apnea syndrome (OSAS), [105,106] extracranial venous hypertension secondary to cardiac septal defect, [107] systemic lupus erythematosus, [108] uremia, [109] iron deficiency anemia [110,111] as well as some endocrine changes such as menstrual irregularities, use of oral contraceptives, hyperthyroidism and hypothyroidism. [112,113] It has also been argued that an underlying thrombophilic defect in patients with IIH might play a role in the pathogenesis and some small studies showed abnormalities in prothrombotic factors.…”
Section: New Insights From Neuro-imaging and Bilateral Transverse Sinmentioning
confidence: 99%